Social Media Marketing dan Experiential Marketing sebagai Pengembangan Usaha Noot Studios - Gheanissa Aulia Luthfani; Rohandi, Mochamad Malik Akbar; Permana, Rezi Muhamad Taufik (Bandung Conference Series: Business and Management, 2024)
Abstract. The fashion industry is growing rapidly due to the influence of technology. Now fashion not only includes grooming, style, and clothing, but can reflect a person's lifestyle and identity. Fashion trends in Indonesia initially tend to imitate western styles that have a simple and practical impression. Korean fashion trends with fashion styles that combine bright colors and cheerful nuances are present and become popular among Indonesians, especially young people. Bags remain a popular fashion product, because bags have an important function in everyday life. Noot Studios, a business brand in the fashion sector, prioritizes its products, namely dumpling bags, which have fashionable and practical values in their use. Dumpling bags have a high selling value because they can answer the needs of people in today's fashionable and practical era. In developing its products, noot studios uses social media marketing as a strategy to introduce products to the market. Experiential marketing is also used as a strategy to build buying interest by inspiring customer emotions through the creation of positive experiences through several events and offline marketing media. Noot Studios uses SWOT Analysis, Porter's Five Forces, Balance Scorecard, Target and Perfomance, and Boston Consulting Group (BCG) Matrix methods in evaluating and creating business development strategies to achieve target markets, build connections with customers and continue to innovate. Abstrak. Industri fashion berkembang pesat karena pengaruh teknologi. Kini fashion tidak hanya meliputi dandanan, gaya, dan busana, tetapi dapat mencerminkan gaya hidup dan identitas seseorang. Tren fashion di Indonesia awalnya cenderung meniru gaya barat yang memiliki kesan simpel dan praktis. Tren fashion korea dengan gaya fashion yang memadukan warna cerah dan nuansa ceria hadir dan menjadi populer di kalangan masyarakat Indonesia terutama anak muda. Tas tetap menjadi produk fashion yang populer, dikarenakan tas memiliki fungsi penting dalam kehidupan sehari-hari. Noot Studios yang merupakan brand usaha di bidang fashion mengutamakan produknya yaitu dumpling bag yang memiliki nilai fashionable dan praktis pada penggunaannya. Dumpling bag memiliki nilai jual yang tinggi karena bisa menjawab kebutuhan masyarakat di era fashionable dan praktis saat ini. Dalam pengembangan produknya, noot studios menggunakan social media marketing sebagai strategi untuk memperkenalkan produk kepada pasar. Experiential marketing juga digunakan sebagai strategi untuk membangun minat beli dengan menginspirasi emosi pelanggan melalui penciptaan pengalaman positif melalui beberapa event dan media pemasaran offline. Noot Studios menggunakan metode SWOT Analysis, Porter’s Five Forces, Balance Scorecard, Target and Perfomance, dan Boston Consulting Group (BCG) Matrix dalam mengevaluasi dan membuat strategi pengembangan bisnis untuk mencapai target pasar, membangun koneksi dengan pelanggan dan terus berinovasi.